Chromatic Number of Pseudo-Von neuman Regular Graph - Arif, Nabeel E.; Khalel, Nermen J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Let R be a commutative ring , the pseudo â€“ von neuman  regular graph of the ring R is define as a graph whose vertex set consists of all elements of R and any two distinct vertices a and b are adjacent if and only if   , this graph denoted by P-VG(R) ,  in this work we got some new results a bout chromatic number of  P-VG(R).